LIFE TRANSFORMATION IN NOVIOLET BULAWAYO’S NOVEL WE NEED NEW NAMES (2013) - Debi Erlanda; Desvalini Anwar (Universitas Negeri Padang, 2019)
This article is about the analysis of novel We Need New Names (2013) by NoViolet Bulawayo that focuses on how the main character has an awareness to transform her life. The problem in this analysis is how far the main character in this novel exposes the issue about life transformation. The aim of this analysis is to find out how far NoViolet Bulawayo’s novel We Need New Names bring ups and reveals the issue of life transformation which is done by the main character in this novel. This analysis involved the fictional devices that are plot (conflict) and setting support the issue of life transformation. This analysis is will deal with the concept of life instinct by Sigmund Freud and the concept of self-awareness by Crisp and Turner.